EFFECT OF USING AMO THEORY ON GHRM ON SERVICE QUALITY WITH OCBE AS MEDIATION IN THE PANDEMIC TIME OF COVID-19 IN INDONESIA, SOE HOSPITAL - Asep Saifudin, M. Havidz Aima, Achmad Hidayat Sutawijaya, Sugiyono (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
During the Corona Virus Pandemic (COVID-19 increasing in Indonesia, this research was conducted to determine the effect of Green Human Resources Management (GHRM) on Service Quality. They used AMO Theory as a GHRM and Organizational Behavior dimension for the Environment (OCBE) as a mediating variable. They were proven to have a positive and significant influence on Service Quality. This study's service variables use the dimensions of Quality Healthcare Service Quality (HEALTHQUAL) to test its application in hospitals owned by Indonesian State Own Enterprise (SOE). With a large respondent of 1004 respondents, the study was conducted in 19 hospitals in 19 cities/regencies in Indonesia. With the Variance Based Structural Equation Modeling (VB-SEM) method, the data is processed using SmartPLS (Partial Least Square).